Penerapan TKDN Dalam Pengadaan Pemerintah dan Implikasinya Terhadap Persaingan Usaha - Ardiana, Oktavia Dwi; Azzahra, Dinda; Sachmaso, Hana Humaira; Fawwaz, Razky (Media Hukum Indonesia (MHI), 2025)
The Domestic Component Level (TKDN) policy in government procurement of goods and services is designed as a strategic instrument to strengthen national industry, promote economic self-reliance, and reduce dependence on imported products. However, its implementation raises complex issues between the interests of industrial protection and the principles of fair business competition as regulated under Law No. 5 of 1999. This research employs a normative juridical method with statutory and conceptual approaches to analyze the balance between the government’s affirmative policy and the obligation to maintain a fair competitive climate. The findings indicate that the implementation of TKDN often serves as a market entry barrier for small enterprises and creates opportunities for abuse, such as the falsification of TKDN certificates. Therefore, strengthening procurement governance and law enforcement is essential to ensure that the TKDN policy is not misused and remains aligned with the objectives of national economic development. This study recommends cross-institutional synergy, enhanced digital transparency, and strict sanctions for violations to realize a clean and integrity-based government procurement system.